Degradation of γ-irradiated polyethylene-ethylene vinyl alcohol-polyethylene multilayer films: An ESR study. (December 2015) - Audran, Gérard; Dorey, Samuel; Dupuy, Nathalie; Gaston, Fanny; Marque, Sylvain R.A.
Abstract: The present work aims to investigate by ESR the effects of γ-irradiation on antioxidants and on solid multilayer films used in biomedical applications. The multilayer films analyzed here are mainly composed of polyethylene and ethylene vinyl alcohol. Radical species are monitored over time after γ-irradiation at several doses (30, 50, 115 and 270 kGy) using ESR to assess the impact of the dose-value on the formation of the radicals.